Comparison of Fatty Acid Profile and Lipid Quality Indices of Local Brackish Water Fish, and Imported Marine Fish Consumed in Benin - Martinien Hospice Mahussi ASSOGBA; Assouan Gabriel Bonou; Chakirath Folakè Arikè Salifou; Mahamadou Dahouda; Antoine Chikou; Souaïbou Farougou; Caroline Douny; Marie-Louise Scippo; Issaka Youssao Abdou Karim (Journal of Food Innovation, Nutrition, and Environmental Sciences)
In Benin, there is limited data on the nutritional composition of commonly consumed fish, particularly their fatty acid profiles. This study aimed to compare the fatty acid composition and nutritional lipid indices of brackish water fish (Coptodon guineensis and Sarotherodon melanotheron) harvested from acadjas with those of imported, frozen seawater fish (Scomber scombrus and Trachurus trachurus) consumed in Benin. Fatty acids were extracted from fish flesh (n=20) and analyzed using gas chromatography-mass spectrometry (GC-MS). Palmitic and oleic acids were the most abundant saturated (SFA) and monounsaturated fatty acids (MUFA), respectively. Marine fish contained significantly higher levels of oleic acid (p<0.05), while brackish fish had higher levels of arachidonic and linoleic acids (n-6 PUFA). Alpha-linolenic acid (ALA) was only detectable in brackish fish, whereas marine fish had significantly higher eicosapentaenoic acid (EPA) and similar docosahexaenoic acid (DHA) levels. The atherogenic index (AI) was highest in S. scombrus (p<0.05), suggesting possible cardiovascular risks with frequent consumption. These findings underscore the nutritional distinctions between locally sourced and imported fish and provide insight for dietary planning and food policy in Benin.